Beyond the pond: Terrestrial habitat use by frogs in a changing climate. (September 2020) - Evans, Maldwyn J.; Scheele, Benjamin C.; Westgate, Martin J.; Yebra, Marta; Newport, Jenny S.; Manning, Adrian D.
Abstract: Amphibians are proportionately over-represented in the current wave of global biodiversity loss. Disease and habitat loss are implicated in many amphibian species declines, but amphibians are also predicted to be sensitive to changes in climate, particularly changes in temperature and loss of moisture. These changes could severely impact frog use of terrestrial habitats. We used data from a long-term (2007–18) landscape-scale experiment in south-eastern Australia to test the effects of terrestrial habitat characteristics and restoration treatments on frog species. We found declines in species richness and in the occurrences of two locally-common species ( Limnodynastes tasmaniensis and Uperoleia laevigata ). These declines were associated with high maximum temperatures, low minimum temperatures and low rainfall. Coarse woody debris addition was associated with higher species richness and L. tasmaniensis occurrence, but this effect was not greater in times of reduced rainfall and high maximum temperatures, implying a weak 'refugia' effect. Frogs were positively associated with wetter sites, and this association increased with higher maximum temperatures. Our findings add to a growing body of evidence that show that prolonged periods of drought pose a key threat to frog populations and that short periods of relief from drought conditions are insufficient to allow recovery of terrestrial frog populations over the long term. Restoration efforts could include the provision of coarse woody debris and should also ensure that good quality aquatic habitat, such as drought-resistant ponds and dams, are available throughout hot and dry times as a supplement to ephemeral aquatic habitat.